The Influence of Using Interactive Media on Middle School Students' Ability to Understand Folklore Texts - Aisyah Eka Alfina; Munirah Munirah; Desy Ayu Andhira (Edumaspul: Jurnal Pendidikan, 2024)
Abstrak This type of research is quantitative with an experimental research design. The aim of this research is to determine the results of media use interactive in increase motivation Study And ability understand Folklore text structure in Indonesian language learning. Population in This research consisted of class VII students at SMP Negeri 6 Barru with a selected sample class VII.1 JUNIOR HIGH SCHOOL Country 6 Barru. Technique collection data that is with using observation, tests ( pretest and posttest ) and questionnaires. Data What was collected was data regarding descriptive analysis and inferential analysis with testing hypothesis use t- test . Results analysis descriptive shows that there is a significant increase after using the media interactive with a percentage of 62.54% or 16 students who obtained excellent marks tall. Whereas results analysis inferential by using formula t- test obtain mark t count =16.46 And t table = 2.05, become t count >t table or 16.46 >2.05. H o is rejected and H 1 is accepted, so it can be concluded that utilization Interactive media influences learning motivation and ability to understand student